(3GdOQI GdSfjI aj PcQ GdOhdI GdMSfjIs - (3CHh YHO Gddg eMeO Hf WGgQ Hf Ydj Hf YjSi GdNRQLj GdOGfj GdCfOdSj GdfMhj GdeGdcjs
(3ChdgG (B:s
(3fMeOc jG ef JLdi ai JLdjI GdYXeI hGdcHQjGA hHYO , abO LQi ai HYV GdCfOdjI PcQ CQHGH GdOhdI GdMSfjI Cf CVY cJGHkG jJVef PcQ cHjQ gPg GdOhdg s
(3BNQgG (B:s
(3abdJ dUGMHi Jcajc gPg GdfHPg hjMUd ef GdCeQ RjOg abdJ dUGMHi gP GcJajJ abGd Ci hQH GdHjJ hcGf gPG BNQ GdYO Hjfi hHjfg s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde VHWs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN WdYJ (B2000) s
Keywords: (3GdJGQjNs